1999
DOI: 10.1097/00003246-199911000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome: Frequency, clinical course, and costs of care

Abstract: The outcome of ARDS is unpredictable at the time of onset and also at the time of the worst oxygenation. Keeping the inspiratory pressures low (30-35 cm H2O [2.94 to 3.43 kPa]) reduces the frequency of pneumothorax, and might lower the mortality. Most patients are young, and therefore the costs per saved year of life are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
68
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 28 publications
12
68
1
2
Order By: Relevance
“…One of the most frequently studied indices is the Pa,O 2 / FI,O 2 , although contradictory results concerning its ability to predict outcome have been reported in adult AHRF/ARDS [2,[27][28][29][30][31][32][33][34][35]. Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently studied indices is the Pa,O 2 / FI,O 2 , although contradictory results concerning its ability to predict outcome have been reported in adult AHRF/ARDS [2,[27][28][29][30][31][32][33][34][35]. Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings strongly suggest that changes in the Ang-Tie2 system, together with elevated VEGF expression, are involved in the development of VILI (figure 4) (Hegeman et al, 2010). An intriguing clinical observation is that most critically ill ALI/ARDS patients do not succumb to acute lung failure but rather to progressive non-pulmonary organ dysfunction, so-called MOF (Ferring & Vincent, 1997;Montgomery et al, 1985;Valta et al, 1999). In this respect, we showed that mechanical ventilation with high pressures increased the pro-inflammatory state of the lung but also of the liver and kidney (figure 1) (Hegeman et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…An important clinical observation is that most ventilated critically ill patients do not succumb to acute respiratory failure but rather to progressive multiple organ failure (MOF) (Ferring & Vincent, 1997;Montgomery et al, 1985;Valta et al, 1999). A definition of MOF has been provided by John Marshall, who defined it as "the development of potentially reversible physiologic derangement involving two or more organ systems not involved in the disorder that resulted in ICU admission, and arising in the wake of a potentially lifethreatening physiologic insult" (Marshall, 2001).…”
Section: Local Versus Systemic Inflammationmentioning
confidence: 99%
“…Although the prevalence is between 1 to 15 percent, but its association with increased mortality risk for these patients is approximately 78% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory failure and invasive treatments such as mechanical ventilation can lead to worsening renal failure, increased mortality, and increased length of stay in the hospital [3]. Valta et al (1999) conducted a study and showed that among 50 children who were bedridden in PICU under mechanical ventilation, 12.8 percent of them had creatinine increase 1.5 times more than the amount before ventilation after 24 hours.…”
Section: Introductionmentioning
confidence: 99%